The tiny seed - Carle, Eric. (Natick, MA : Picture Book Studio : Distributed in USA by Alphabet Press, 1987)
A simple description of a flowering plant's life cycle through the seasons.
Reprint. Originally published: New York : Crowell, 1970.
Booklist
3.2
K-3
K-3
Keywords: Plant life cycles -- Juvenile literature; Plants -- Juvenile literature; Seeds -- Juvenile literature; Seeds -- Dispersal -- Juvenile literature; Plants; Seeds -- Dispersal; Plants; Seeds